KHASIAT WORTEL TERHADAP TEKANAN DARAH PADA PENDERITA HIPERTENSI (STUDI KASUS DI DESA BULUSULUR, WONOGIRI) - Nita Yunianti Ratnasari; Alviatianshi Meilasari (Jurnal Keperawatan GSH, 2021)
Background: Hypertension is a disease of high blood pressure which when measured with a sphygmomanometer the results exceed the normal value, which is more than 120/80 mmHg (millimeters of mercury). Hypertension can also be called the "silent killer". The signs of hypertension can be known by measuring blood pressure and the complaints suffered by the patient are usually headaches, a feeling of heaviness in the neck, and easy emotions. Vegetable Carrots have various properties to cure diseases, not to forget that carrots can reduce high blood pressure. Compounds that can reduce it are carotenoids which function as antioxidants that can neutralize free radicals, one of the risks of hypertension, namely cardiovascular disease, can be prevented. Not only that, the mineral content in carrots, namely potassium, also functions to maintain water balance in the body, neutralize acids in the blood, and can lower blood pressure. Objective: It has been obtained from previous experience which also uses carrot vegetables to treat blood pressure in people with hypertension. Method: Using descriptive technique with case study approach. The author only uses 3 respondents as a case study. Result: the respondent's high blood pressure decreased even though there was not much decrease. Conclusion: From all respondents said that respondents feel dizzy and pain in the neck.From this problem, the authors took action to provide carrot herbal therapy to reduce high blood pressure for people with hypertension.